(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Cervical cancer is the leading cause of cancer-related deaths among women in Kenya. Patients present late when the cure is unattainable and have an impaired quality of life (QoL). Pain is the worst and most common cause of impaired QoL. Poor control is due to a focus on the physical aspect of pain only rather than the holistic approach that also considers the nonphysical factors, including psychological, social, spiritual, economic, and information needs aspects of pain. Information need is defined as a state in which one perceives a gap between information and knowledge available to solve a problem. There is inadequate information exchange between health care providers and cervical cancer patients in Kenya, with such patients reporting that inadequate information prolonged their suffering as they sought diagnosis and treatment. There have been recommendations that communication guidelines be developed, and communication training skills be developed in a culturally relevant way. Differences in cultural and socioeconomic contexts may impede this goal. Objective: To explore information needs factors among patients with cervical cancer stages III and IV at the Kenyatta National Hospital. Methods: Qualitative research using a descriptive phenomenological study involving fifteen in-depth interviews and five focus group discussions was conducted. Results: This study revealed poor methods of breaking bad news, conflicts in the disclosure of bad news to patients, inadequate information on the investigations and procedures needed, and doctors’ unavailability to provide detailed information, especially those that require seeking money from relatives. Conclusion: Information needs remain a gap affecting pain experienced by cervical cancer patients.